The Influence of a STEM-Based Approach on the Students’ Academic Achievement in Genetics (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research explored the impact of a STEM-based approach on the academic achievement of the grade 8 students in genetics. By incorporating Science, Technology, Engineering, and Mathematics (STEM) into genetics teaching, the study aimed at investigating the potential of a STEM-based approach as a teaching strategy in establishing fundamental concepts and deepen understanding of genetics, and improve their academic achievement in a specific period by using the researcher-developed and validated training packet in genetics. A quasi-experimental design was employed, featuring pre-test and post-test evaluations of two groups: one taught through conventional methods and the other with STEM-based techniques. The results revealed a notable enhancement in the academic achievement of students who were taught using the STEM method, demonstrating its effectiveness in promoting critical thinking, problem-solving, and collaboration. These findings highlighted the transformative potential of STEM approaches in reshaping science lessons and equipping students for the challenges of the 21st century.